(untitled) (Revista Electrónica REDINE, 2022)
The main objective of this study was to record and analyze the linguistic domain, reading habits and the application of reading strategies in English and Spanish university students enrolled in English for specific purposes (ESP) courses at a western Venezuela university. Our theoretical base proposes an update of the transactional learning perspective (Ausubel, Novak et al., 1983) and the historical sociocultural learning theory (Vygotsky, 2008, 1979). The data was collected through a cross-sectional study during 2009-2016/2018-2021 through the application of a survey with open responses in the first class of each academic semester to different groups of students at UNESUR without any prior preparation. The sample consisted of 1207 participants. The information collected was processed through the use of traditional descriptive statistical processes. The results reveal that the students of ESP courses (a) predominantly show a poor lexical-syntactic domain of the foreign language (FL); (b) show a predilection for short texts in simple language that usually appear in daily publications such as newspapers and magazines; (c) use reading strategies infrequently and this affects the use of the contents studied; (d) demonstrate knowledge of certain reading strategies (skimming, scanning, summarizing, recognition of linguistic and syntactic cues) although they gradually preferred not to use them in their readings. These fundamental findings allow us to infer that students, in general, do not take complete advantage of the strategies known by them or use them incorrectly, and this is reflected in their reading comprehension and general academic performance. Likewise, students must receive in ESP courses, on a constant basis, effective instruction on the strategies they can use to read academic texts in their native language (L1) and in a foreign language (FL) in order to improve their comprehensive results in the academic reading process.